THE SOMATIC PHRASEOLOGISMS IN THE EPIC "ER ZIYWAR" - Allambergenova , Gulzhakhan; Allamuratov, Miyrbek (Innovative Development in Educational Activities, 2023)
In any literary works, the types of somatic idioms related to human parts such as head, hands, eyes, feet, and ears are often exaggerated, because these parts of a person are the most active and are more visible in action. In the epic "Er Ziywar", the above mentioned types of somatic phraseology often occur. In the article, the views on somatic phraseology in the epic "Er Ziywar" were analyzed based on scientific evidence.